De la síntesis con Agrupaciones Lineales a la síntesis con Agrupaciones Circulares - Suarez Fajardo, Carlos Arturo; Bataller, Miguel Ferrando; Valero Nogueira, Alejandro; Eduardo Gaona, Elvis; Rincón Reyes, Diego Yecid (Ingeniería, 2008)
This article seeks to make an extension of some of the analytic methods of synthesis commonly used in the lineal arrays to the case of the circular arrays with isotropic and directive elements. The study will be made with ideal directive elements like cardioids, with several orders.